Multi-criteria comparison of nuclear reactors using the MULTIMOORA method: A case of study for Chile. (August 2021) - Fernández, Claudio; Vergara, Julio
Abstract: Technology selection is a major issue in nuclear power since it restrains further options. Once generally accepted by society, a methodology is needed to analyze and synthetize multidimensional parameters for an optimum selection. The International Atomic Energy Agency has developed Comparison criteria for innovative reactors and fuel cycles. Our task was to develop an extension of the Multi-Objective Optimization by Ratio Analysis (MULTIMOORA) for advanced nuclear reactor prioritization in developing countries. The objective of this work was to apply such multi-criteria analysis technique for decision making to a Chilean nuclear power programme based on policy recommendations. We selected a list of conceptual designs recognized by the Agency that were compatible with Chilean energy needs, applying the IAEA's INPRO methodology and proposing three priority sets, and we obtained Performance Rankings for those. Based on anticipated parameters, NuScale and EC6 reactors stood high based on their performance opposed by the ACP100 and VVER600 reactors. The SMART and SVBR100 reactors were sensitive to the priority set, as devised. Our model performed reasonably and needs further proofs for extended scenarios and conditions. Highlights: MCA techniques are suitable for comparing nuclear reactors. MULTIMOORA methodology is compatible with IAEA methodology. Priority sets strongly influence the results of the comparison. Safety measures of advanced reactors are compatible with Chile requirements. Comparative ranking shows dominance of NuScale and EC-6 reactors.